Digital Reform of The Education Industry in The Post-Epidemic Era - Lin, Wangke (International Journal of Management and Education in Human Development, 2022)
In response to the outbreak of the COVID-19 epidemic, an unprecedented online education practice was launched nationwide, accelerating the education transformation. At present, epidemic prevention and control have entered a stage of normalization. How to promote the continuous and in-depth development of digital education in the "post-epidemic era" is a matter of great concern to the education system and the entire society. Digital application has changed the traditional education management system, from offline to online, so that the learning of the master is no longer restricted by region. Word-based education has promoted education and teaching reforms in different aspects, bringing more and more experience and enlightenment to the construction of digital campuses in the future, and also providing a strong guarantee for students' home learning. At the same time, digital application training promotes teacher professional development, and is spawning a new teacher professional role and ability structure.